МОТИВ ИГРЫ В СТРУКТУРЕ РОМАНОВ «ВОЙНА И МИР» Л.Н. ТОЛСТОГО И «БРАТЬЯ КАРАМАЗОВЫ» Ф.М. ДОСТОЕВСКОГО (Filološke pripombe, 2019)
The article deals with different meanings of the motif of play in the novel “War and Peace” by Tolstoy and “The Brothers Karamazov” by Dostoevsky in the context of the common features of aesthetics and ethics of these writers. The attempted analysis shows that the motif of play occupies an important place in the structure of the images of the negative characters: Napoleon in the novel of Tolstoy and Fyodor Pavlovich Karamazov in the novel of Dostoevsky. Thus, this motif is closely related to the central concepts of the novels: the war in “War and Peace” and “Karamazovschina” in “The Brothers Karamazov”.